Legal Protection for Consumers in E-Commerce Transactions Through Facebook Marketplace with Split Payment System - Ningsih, Sri Eva; Arpangi, Arpangi (Jurnal Hukum Khaira Ummah, 2025)
Abstract. In today's era, technology is something that is very much needed by every group, the use of technology brings positive forms to facilitate communication and so on, but the use of technology is often misused such as electronic-based fraud or what we often know as e-commerce. Electronic commerce (e-commerce) has now reformed conventional trade, where the interaction between consumers and business actors that was previously carried out directly, which with the existence of electronic commerce, has now become an indirect interaction. The definition of e-commerce is also stated in Article 1 paragraph (2) of the ITE Law (Information and Electronic Transactions) No. 11 of 2008 which regulates, "Electronic Transactions are legal acts carried out using Computers, Computer networks, and/or other electronic media". The method used is the normative legal approach method. With research specifications using normative descriptive, where using secondary data is analyzed qualitatively. The formulation of the problem is analyzed based on the theory of legal certainty and the theory of law enforcement. The results of the study show that there are no clear rules governing the split payment system to be a legal umbrella that can protect consumers in making online buying and selling transactions using the Marketplace feature on the Facebook application which allows consumers to suffer losses due to business actors in the application. Law No. 8 of 1999 concerning Consumer Protection (UUPK) and the ITE Law are laws that regulate consumer protection and also online transactions. As a business actor, it is his obligation to provide and fulfill the rights of his consumers. Thus, consumers will get their rights as consumers and will not be harmed by business actors who commit bad acts.